Interleukin-17A Causes Osteoarthritis-Like Transcriptional Changes in Human Osteoarthritis-Derived Chondrocytes and Synovial Fibroblasts In Vitro - Mimpen, Jolet Y.; Baldwin, Mathew J.; Cribbs, Adam P.; Philpott, Martin; Carr, Andrew J.; Dakin, Stephanie G.; Snelling, Sarah J.B. (Frontiers in Immunology, 2021)
Increased interleukin (IL)-17A has been identified in joints affected by osteoarthritis (OA), but it is unclear how IL-17A, and its family members IL-17AF and IL-17F, can contribute to human OA pathophysiology. Therefore, we aimed to evaluate the gene expression and signalling pathway activation effects of the different IL-17 family members in chondrocytes and synovial fibroblasts derived from cartilage and synovium of patients with end-stage knee OA. Immunohistochemistry staining confirmed that IL-17 receptors A (IL-17RA) and IL-17RC are expressed in end-stage OA-derived cartilage and synovium. Chondrocytes and synovial fibroblasts derived from end-stage OA patients were treated with IL-17A, IL-17AF, or IL-17F, and gene expression was assessed with bulk RNA-Seq. Hallmark pathway analysis showed that IL-17 cytokines regulated several OA pathophysiology-related pathways including immune-, angiogenesis-, and complement-pathways in both chondrocytes and synovial fibroblasts derived from end-stage OA patients. While overall IL-17A induced the strongest transcriptional response, followed by IL-17AF and IL-17F, not all genes followed this pattern. Disease-Gene Network analysis revealed that IL-17A-related changes in gene expression in these cells are associated with experimental arthritis, knee arthritis, and musculoskeletal disease gene-sets. Western blot analysis confirmed that IL-17A significantly activates p38 and p65 NF-B. Incubation of chondrocytes and synovial fibroblasts with anti-IL-17A monoclonal antibody secukinumab significantly inhibited IL-17A-induced gene expression. In conclusion, the association of IL-17-induced transcriptional changes with arthritic gene-sets supports a role for IL-17A in OA pathophysiology. Future studies should further investigate the role of IL-17A in the OA joint to establish whether anti-IL-17 treatment could be a potential therapeutic option in OA patients with an inflammatory phenotype.